Interactions of Human hMSH2 with hMSH3 and hMSH2 with hMSH6: Examination of Mutations Found in Hereditary Nonpolyposis Colorectal Cancer - Guerrette, Shawn (American Society for Microbiology, 1998)
Mutations in the human mismatch repair protein hMSH2 have been found to cosegregate with hereditary nonpolyposis colorectal cancer (HNPCC). Previous biochemical and physical studies have shown that hMSH2 forms specific mispair binding complexes with hMSH3 and hMSH6. We have further characterized these protein interactions by mapping the contact regions within the hMSH2-hMSH3 and the hMSH2-hMSH6 heterodimers. We demonstrate that there are at least two distinct interaction regions of hMSH2 with hMSH3 and hMSH2 with hMSH6. Interestingly, the interaction regions of hMSH2 with either hMSH3 or hMSH6 are identical and there is a coordinated linear orientation of these regions. We examined several missense alterations of hMSH2 found in HNPCC kindreds that are contained within the consensus interaction regions. None of these missense mutations displayed a defect in protein-protein interaction. These data support the notion that these HNPCC-associated mutations may affect some other function of the heterodimeric complexes than simply the static interaction of hMSH2 with hMSH3 or hMSH2 with hMSH6.